O desenvolvimento do pensamento algébrico em uma formação continuada de professores no contexto da educação inclusiva - Santos, Everton Odair dos (2022)
In this work we present a research with a qualitative approach whose objective is to identify the perception of teachers about the development of algebraic thinking in basic education students. And it has as its guiding question: what are the perceptions of teachers who teach mathematics in relation to the development of algebraic thinking? For this, we use as references Radford, Almeida and Santos, who discuss typologies and stages of development of such thought. And we examined the answers given by course teachers in relation to the development of algebraic thinking with the use of mobile applications. The data of this research come from a continuous formation proposed by the research group of the Pontifical Catholic University of São Paulo – PUC-SP: Professor of Mathematics: Formation, profession, knowledge and teaching work, under the coordination of Professor Dr. Ana Lucia Manrique. The training proposed exploring and discussing the uses of new technologies and teaching and learning processes in Mathematics from an inclusive perspective, involving algebraic content. In this sense, this research sought in its results to expose perceptions about the development of algebraic thinking in the context of inclusive education and to analyze the responses of teacher-students in relation to the continuing education offered, which involved activities with cell phone applications designed with an inclusive perspective. In this way, we adopt inclusive education as a form of respect for human diversity, extrapolating the idea that inclusive education is solely focused on actions for people with disabilities